If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + -12 = 5m Reorder the terms: -12 + 8m = 5m Solving -12 + 8m = 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. -12 + 8m + -5m = 5m + -5m Combine like terms: 8m + -5m = 3m -12 + 3m = 5m + -5m Combine like terms: 5m + -5m = 0 -12 + 3m = 0 Add '12' to each side of the equation. -12 + 12 + 3m = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 3m = 0 + 12 3m = 0 + 12 Combine like terms: 0 + 12 = 12 3m = 12 Divide each side by '3'. m = 4 Simplifying m = 4
| 81x^8-82x^4+1=0 | | 2X+4.5Y=10 | | (D^3-3D^2+4)x=0 | | x^2+14x+14+y^2-2y=0 | | Y=-0.7x+340 | | 8x^3-12x^2-2x+3=0eq | | 10(s-8)=-125 | | (40-x)(16-x)=340 | | 12-1/3x=x | | 33-4x=9-9x | | 300-56x-x^2=0 | | x=12-1/3x | | 3x-4=11x-67 | | 0.56x+x=220 | | 0.2x+x=220 | | X+10+7x=-15-2x | | x^3=168 | | 7(4s)+1=231 | | 4(2l)+6=24 | | 1.8x=6.6 | | 14x^2-84x-126=0 | | (u-7)*8=24 | | 1/9x^6-81=0 | | 12=56-2*(3*x+4) | | 2u+14=4 | | f(e-a-c)=e(f-b-(1000-c)) | | Y=12x^2-6x | | 4x+(-3+7x)= | | 15=d/-15 | | X(x-2)+2=11-2x | | 45=12-11a | | f(x)=-6/-x-6 |